2023
DOI: 10.1007/s00223-023-01096-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone and the Unfolded Protein Response: In Sickness and in Health

Abstract: Differentiation and optimal function of osteoblasts and osteoclasts are contingent on synthesis and maintenance of a healthy proteome. Impaired and/or altered secretory capacity of these skeletal cells is a primary driver of most skeletal diseases. The endoplasmic reticulum (ER) orchestrates the folding and maturation of membrane as well as secreted proteins at high rates within a calcium rich and oxidative organellar niche. Three ER membrane proteins monitor fidelity of protein processing in the ER and initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…Consequently, the direct binding of mature XBP1 to these sites stimulates the transcription of Nfatc1, thereby facilitating the promotion of osteoclast formation ( Figure 2 ). Moreover, it was observed that ER stress was only transiently induced following RANKL stimulation, indicating that the role of the UPR in maintaining mature osteoclast function is limited ( 17 , 32 ).…”
Section: Regulation Of Xbp1 In Osteoclast Differentiationmentioning
confidence: 99%
“…Consequently, the direct binding of mature XBP1 to these sites stimulates the transcription of Nfatc1, thereby facilitating the promotion of osteoclast formation ( Figure 2 ). Moreover, it was observed that ER stress was only transiently induced following RANKL stimulation, indicating that the role of the UPR in maintaining mature osteoclast function is limited ( 17 , 32 ).…”
Section: Regulation Of Xbp1 In Osteoclast Differentiationmentioning
confidence: 99%